Intraoperative Tumor Imaging with Indocyanine Green in Head and Neck Cancer Patients. (2nd September 2014) - Chung, Thomas K.; Kovar, Joy; Bell, Walter; Brandwein‐Gensler, Margaret; Rosenthal, Eben L.
Abstract : Objectives: (1) Describe the effectiveness of indocyanine green (ICG) as an imaging agent for head and neck tumors. (2) Illustrate the potential of near‐infrared imaging for intraoperative visualization of cancers. Methods: Patients underwent intravenous administration of 7.5mg ICG during the surgical procedure. The SPY/LUNA (Novadaq) near‐infrared intraoperative imaging system was used prior to resection and the Pearl (LICOR) and Odyssey (LICOR) systems for ex‐vivo tumor imaging. Tumor‐to‐background ratio (TBR) was defined as tumor fluorescence divided by normal tissue fluorescence. Histologic analysis was performed with a head and neck cancer board‐certified pathologist. Results: Five patients were enrolled into this study between August and September 2013. Three patients had pharyngeal cancer, one had laryngeal cancer, and one had cutaneous cancer. TBR values of confirmed cancer tissue varied among patients (LUNA TBR 3‐9, Pearl TBR 3‐18). However, in 2 patients, areas of highest fluorescence were found to be absent of carcinoma on histological analysis. The epidermal portions of the cutaneous SCC lesion were highly fluorescent, but the tumor did not penetrate this layer in multiple sections. Histologic analysis of these tissues confirmed significant areas of acute and chronic inflammation at areas of high fluorescence intensity. Skin, mucosal surfaces, and perivascular areas were most prone to false‐positive high fluorescence. Conclusions: While intravenous ICG does accumulate in head and neck tumors sufficiently to distinguish them from normal tissue, it is not specific enough to serve as a tumor visualization agent. Targeted fluorescent probes will likely be needed for image‐guided surgery.